He Knows Too Much - Maley A. Alan (Cambridge english readers Level 6)
An English compy executive in India, Dick Stirling, is dismissed after he tries to unveil corruption within his company. His life falls apart and his marriage breaks up. He then sets out on a one-man quest for the truth behind his dismissal. His search takes him back to the rich mystery and beauty of India and he is finally forced to choose between love and revenge